2012
DOI: 10.2340/00015555-1247
|View full text |Cite
|
Sign up to set email alerts
|

Contact Allergy to Gold in Patients with Oral Lichen Lesions

Abstract: The aetiology of oral lichen lesions is obscure. In this study the frequency of contact allergy to gold in 83 patients with oral lichen lesions was compared with that in two control groups, comprising 319 age- and gender-matched patients with dermatitis selected from files and 83 clinically examined dermatitis patients. All patients were tested epicutaneously with gold sodium thiosulphate. The two control groups tested were under examination for a tentative diagnosis of allergic dermatitis not related to oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
4
16
0
Order By: Relevance
“…Dental technicians are, on a daily basis, exposed to alloys and tools that contain skin sensitizing metals. Most studies concerning dentistry and metals have considered the effect of metal release from dental restorations on the health of patients (20,26,27). Several studies, reviewed by Leggat et al, have been concerned with the health of dental workers (28).…”
Section: Metal Releasementioning
confidence: 99%
“…Dental technicians are, on a daily basis, exposed to alloys and tools that contain skin sensitizing metals. Most studies concerning dentistry and metals have considered the effect of metal release from dental restorations on the health of patients (20,26,27). Several studies, reviewed by Leggat et al, have been concerned with the health of dental workers (28).…”
Section: Metal Releasementioning
confidence: 99%
“…4 It is strongly indicated that slow leaching of gold salts in the oral cavity may provoke an allergic reaction and trigger oral lichen planus. 5 Gold therapy may induce various adverse skin reactions including systemic contact dermatitis, which may occur in contact-sensitized persons when they are exposed to the haptens systemically. 6 There are published cases of lichenoid dermatitis after consumption of gold-containing liquor.…”
Section: Discussionmentioning
confidence: 99%
“…Positive patch testing to gold sodium thiosulfate has been noted in a subset of OLP patients [3,18]. A large study found positive patch testing to nickel and palladium metals in approximately a quarter of OLP patients [15].…”
Section: Oral Lichen Planus and Oral Lichenoid Lesionsmentioning
confidence: 98%